MYSTICO-PHILOSOPHY - Ngainun Naim (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2018)
This article aims to offer an epistemological concept on scientific integration between religious and secular sciences proposed by a prominent Indonesian thinker Mulyadhi Kertanegara. The scientific integration (integrasi keilmuan) is essential concept explaining a contemporary development of Indonesian-state Islamic universities as exemplified by institutional transformation from exclusively Islamic studies learning institution of State Islamic Institute for Islamic Studies/IAIN to scientific integration of State Islamic University/UIN. As this article argues, let alone the institutional transformation, philosophical transformation of Islamic higher educational learning is a crucial element. It is the foundation of the institutional transformation and is still a major problem for contemporary Indonesian Islamic higher education. This article further argues that the philosophical transformation includes the construction of scientific and academic cultures and tradition which are applicable to contemporary Indonesian Islam higher educational system. Taking a root to the concepts of Islamic philosophy, Mulyadhi Kartanegara’s mystical-philosophical concept is indeed an innovative offer which is crucial as an alternative foundation of contemporary transformation of Islamic higher education in Indonesia and an answer to scientific debates on the relationship between religion and secular science.